The impact of paraspinal muscle morphology on functional outcome in patients with degenerative lumbar spine disease undergoing surgery - A prospective observational study - Niraj Ghimire; Prashant Lakhe; Anil Kumar; Nisha Ghimire; Chayanika Kutum; Deepak Choudhary; Bhanu Pratap Singh Chauhan; Poonam Narang; Hukum Singh; Daljit Singh (Brain and Spine, 2024)
Introduction: Paraspinal muscle atrophy has been implicated in low back pain (LBP) as well as degenerative disc disease, lumbar spinal stenosis, and disc herniation. The objective of the study was to determine the association of paraspinal muscle morphology with functional outcomes in patients undergoing spine surgery in degenerative spine diseases. Research question: Can the degree of paraspinal muscle atrophy be a reliable prognostic indicator of post-operative functional outcome in patients undergoing surgery for degenerative lumbar spine disease? Materials and methods: Forty-one patients with degenerative lumbar spine disease planned for surgery were included. Pre-operative and postoperative MRI-based muscle morphology including total cross-sectional area (TCSA) and muscle atrophy were recorded. Association between muscle parameters and functional status as indicated from the visual analogue scale (VAS), and Oswestry Disability Index (ODI) were assessed, and compared between prior and after surgery. Results: The MF and ES cross-sectional area on MRI was in proportion to the functional status. (higher ODI and VAS). Preoperative MF TCSA was positively correlated with preoperative ODI ((r = −0.441, p = = 0.032), preoperative VAS (r = −0.338, p = 0.048) and was negatively correlated with change in ODI (r = −0.268, p = 0.016) while preoperative ES TCSA was negatively correlated with preoperative ODI (r = −0.420, p = 0.003). Preoperative ODI, change in ODI and preoperative VAS had significant correlation with muscle atrophy (p < 0.05). There was a positive correlation between preoperative ODI with Grade 2 (r = 0.332, p = 0.016) and Grade 3 (r = 0.299, p = 0.048) MF muscle; and Grade 2 (r = 0.308, p = 0.067) and Grade 3 (r = 0.202, p = 0.018) ES muscles atrophy. The change in ODI, negatively correlated with Grade 3 MF and ES atrophy (r = −0.332, p = 0.018 and r = −0.286, P = 0.011 respectively). Linear regression analysis showed duration of symptom (p = 0.005) was positively associated with preoperative ODI. Age and BMI were negatively associated with improvement in ODI. (p = 0.073, 0.098 respectively). Discussion and conclusion: Preoperative paraspinal muscle area is an independent variable that affects preoperative functional status. The grade of paraspinal muscle atrophy is a good predictor of preoperative, postoperative and improvement in functional status.